2012
DOI: 10.3897/zookeys.182.2720
|View full text |Cite
|
Sign up to set email alerts
|

Annotated type catalogue of the Bothriembryontidae and Odontostomidae (Mollusca, Gastropoda, Orthalicoidea) in the Natural History Museum, London

Abstract: The type status is described for specimens of 84 taxa classified within the families Bothriembryontidae and Odontostomidae (superfamily Orthalicoidea ) and kept in the Natural History Museum, London. Lectotypes are designated for Bulimus (Liparus) brazieri Angas, 1871; Bulimus broderipii Sowerby I, 1832; Bulimus fuligineus Pfeiffer, 1853; Helix guar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 21 publications
(31 reference statements)
0
24
0
Order By: Relevance
“…According to Breure and Ablett (2012) this species is a subjective synonym of Plectostylus broderipii . The specimens here examined seem slightly different; the shells are more elongated, with a larger aperture and a more acute spire.…”
Section: Systematicsmentioning
confidence: 99%
“…According to Breure and Ablett (2012) this species is a subjective synonym of Plectostylus broderipii . The specimens here examined seem slightly different; the shells are more elongated, with a larger aperture and a more acute spire.…”
Section: Systematicsmentioning
confidence: 99%
“…Other abbreviations used are: / end of line in cited text; coll., collection; D, diameter; H, shell height; leg., legit , collected; W, number of whorls. For the way measurements on the shell have been taken, see Breure and Ablett (2012: fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…The two specimens from the Dunker collection are very likely also from the same source and are considered probable type material. The lectotype is NHMUK 20100652 (see Breure and Ablett 2012), thus the ZMB material are paralectotypes.…”
Section: Systematicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study we aimed to curate the large Western Australian Museum (WAM) Bothriembryon collection to current taxonomy (Breure and Ablett 2012;Breure and Whisson 2012;Stanisic et al 2018) and to define the geological age of identified Bothriembryon species (where available).…”
Section: Fossil Distributionmentioning
confidence: 99%